Effects of Lactiplantibacillus plantarum and Lacticaseibacillus paracasei supplementation on the faecal metabolome in children with coeliac disease autoimmunity: a randomised, double-blinded placebo-controlled clinical trial - Jenickova, Eliska; Andrén Aronsson, Carin; Mascellani Bergo, Anna; Cinek, Ondrej; Havlik, Jaroslav; Agardh, Daniel (Frontiers in Nutrition, 2023)
Coeliac disease is a lifelong immune-mediated enteropathy manifested as gluten intolerance in individuals carrying specific human leukocyte antigen (HLA) molecules. Other factors than genetics and gluten intake, however, may play a role in triggering the disease. The gut internal environment is thought to be one of these potential contributing factors, and it can be influenced throughout life. Here we examine the impact of Lactiplantibacillus plantarum HEAL9 and Lacticaseibacillus paracasei 8700:2 supplementation on the faecal metabolome in genetically predisposed children having tissue transglutaminase autoantibodies, i.e., coeliac disease autoimmunity. Probiotic strains were selected based on their beneficial properties, including mucosal permeability and immune modulation effects. The intervention group (n=40) and control group (n=38) took the probiotics or placebo daily for 6 months in a double-blinded randomised trial. Faecal samples were collected at baseline and after 3 and 6 months, respectively, and analysed using the 1H NMR for metabolome. The incorporation of 16S rRNA sequencing as a supportive dataset complemented the analysis of the metabolome data. During the 6 months of intervention, the stool concentrations of 4-hydroxyphenylacetate increased in the intervention group as compared to controls, whereas concentrations of threonine, valine, leucine, isoleucine, methionine, phenylalanine, aspartate, and fumarate decreased. The findings suggest a modest yet significant impact of the probiotics on the faecal metabolome, primarily influencing proteolytic processes in the gut. Additionally, a noteworthy effect on the glycine, serine, and threonine metabolic pathway has been observed. Trial registration: ClinicalTrials.gov [Clinical Trials identifier: NCT03176095]